The Impact of Disclosures on Green Accounting, Corporate Social Responsibility, and Corporate Governance on Stock Returns - Safitri, Yasmin; PurwohediMurwanigsari, Unggul; Yusuf, Muhammad (CV. Proaksara Global Transeduka, 2024)
This research investigates the impact of disclosing sustainability reports, encompassing Environmental, Social, and Governance (ESG) aspects, on stock returns. Environmental factors are represented by green accounting, social by corporate social responsibility, and governance by corporate governance. The study employs quantitative methods using secondary data from sustainability reports of companies listed on the ESG Leaders index from 2017 to 2022 (total of 138 samples). Descriptive statistical analysis of panel data using Eviews 12 software was conducted. Results indicate that while green accounting does not significantly influence stock returns, both corporate social responsibility and corporate governance have a positive impact. This study suggests that companies can enhance their ESG reporting to cultivate a positive stakeholder image and potentially increase stock returns.